1980
DOI: 10.1111/j.1439-0450.1980.tb02027.x
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Cattle Vaccinated with Inactivated Oil‐Adjuvant IBR‐ Vaccine Against Experimental Infection

Abstract: Summary Vaccination of four to six months old calves with 2 or 5 ml. of inactivated adjuvant IBR vaccines caused production of low titres of neutralizing serum antibodies. Revaccination with the same doses after four weeks resulted in an increase in titer to 1 : 16 — 1 : 512, and in production of measurable amounts of secretory antibodies. After intranasal administration of 4 × 107.6 TCID50 of virulent virus the vaccinated animals responded by a slight increase in nasal secretion containing a low level of viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 2 publications
2
3
0
Order By: Relevance
“…The potency evaluation of the different prepared formulas of polyvalent viral vaccine in calves represented in table (1,2) revealed that all vaccinated animals developed serum neutralizing antibody titers (SN antibody) expressed as ND reached their peak at first 28 day post inoculation remained stable higher than the minimal acceptable titer of protective level until the end of experiment to the three formulation 1,3and 4. Such data are similar to those obtained by (Bittle, 1968) who recorded that the BVD antibody level 0f 1:8 diluation (ND 0.9) was protective (Zuffa and Feketeova, 1980) and Those authors reported that the minimal acceptable titer of neutralizing antibodies was 1:4 diluation (ND0.6) was protective against IBR, PI-3 and BRS viruses. compared with the control non vaccinated group (group 2) that showed no neutralizing antibody response.…”
Section: Discussionsupporting
confidence: 90%
“…The potency evaluation of the different prepared formulas of polyvalent viral vaccine in calves represented in table (1,2) revealed that all vaccinated animals developed serum neutralizing antibody titers (SN antibody) expressed as ND reached their peak at first 28 day post inoculation remained stable higher than the minimal acceptable titer of protective level until the end of experiment to the three formulation 1,3and 4. Such data are similar to those obtained by (Bittle, 1968) who recorded that the BVD antibody level 0f 1:8 diluation (ND 0.9) was protective (Zuffa and Feketeova, 1980) and Those authors reported that the minimal acceptable titer of neutralizing antibodies was 1:4 diluation (ND0.6) was protective against IBR, PI-3 and BRS viruses. compared with the control non vaccinated group (group 2) that showed no neutralizing antibody response.…”
Section: Discussionsupporting
confidence: 90%
“…application of a large infectious dose. This has confirmed the generally known correlation between the induction of an infection and the size of the infection dose in partially immune cattle (8,28). Under natural conditions, the latent infection state is rarely activated (S), whereby the immunized cattle resist contact infection with small doses of excreted virus.…”
Section: Discussionsupporting
confidence: 77%
“…Therefore, a double vaccination seemed to induce a better immune response than a single vaccination (Bosch et al, 1996). It has been reported that the minimal immunogenic virus neutralizing antibody titer for IBR (BoHV-1) virus was ≥log 10 0.6 (Zuffa and Feketeova, 1980) or 0.9 (USA Code of Federal Regulation, 1987). All vaccinated calves seroconverted to BoHV-1 gB in the 1 st week post vaccination as detected by gB-based ELISA kit.…”
Section: Discussionmentioning
confidence: 97%